2007
DOI: 10.1108/14635770710834491
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking firm performance

Abstract: PurposeThe aim of the paper is to provide a framework for benchmarking firm performance (profitability) using panel data. Further, to illustrate how the estimation results can be used for simulation (what if?) exercises.Design/methodology/approachThe authors apply the econometric techniques used in panel data to estimate profit functions, thereby enabling us to compute measures of firm efficiencies which can subsequently be used as benchmarking tools.FindingsThe results suggest that both large firms and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Smith and Verner (2006) found that the proportion of women in top management jobs had a positive effect on a firm's performance and that the effect depended on the qualifications of female top managers in Denmark. Dawkins et al (2007) argue that both large firms and those which are highly specialized, enjoy higher profit margins, whereas the more capital intensive the firm the lower its profitability.…”
Section: Understanding the Key Conceptsmentioning
confidence: 99%
“…Smith and Verner (2006) found that the proportion of women in top management jobs had a positive effect on a firm's performance and that the effect depended on the qualifications of female top managers in Denmark. Dawkins et al (2007) argue that both large firms and those which are highly specialized, enjoy higher profit margins, whereas the more capital intensive the firm the lower its profitability.…”
Section: Understanding the Key Conceptsmentioning
confidence: 99%
“…For example, Argyris (1977) applies benchmarking to double loop organizational learning and McAdam and McCreedy (1999) to knowledge management initiatives. Furthermore, benchmarking is explicitly referred to in the more tactical areas of total quality management (Franceschini et al, 2006), supply chain management (Deming, 1982;Zairi and Baidoun, 2003), balanced scorecards (Kaplan and Norton, 1992), Six Sigma (Xerox, 1979), innovation (Radnor and Robinson, 2000), performance measurement (Carpinetti and de Melo, 2002;Anderson and McAdam, 2004;Dawkins et al, 2007;Alstete, 2008), and business excellence models (EFQM, 2003;NIST, 2007). These applications refine the definition of benchmarking.…”
Section: 4mentioning
confidence: 99%
“…Studies of this caliber (e.g., Dawkins, Feeny & Harris, 2007;Debnath & Shankar, 2008) explained that benchmarking is a tool that enhances organizational performance. Based on the above, organizations that fail to practice benchmarking as a main process of performance measurement will realize little to no improvement, highly dissatisfied employees and high turnover.…”
Section: Measuring Organizational Performancementioning
confidence: 99%